Molecular diagnosis of Chlamydia trachomatis in infertile Iraqi women using Real time-PCR and comparison with other methods - Mohammed, Iqbal Harbi; Al-Awadei, Salwa J.; K.Saadedin, Shurook.M. (Iraqi Journal of Science, 2021)
Chlamydia trachomatis is the most common of negative gram bacteria that cause sexually transmitted diseases. It affects the reproductive system in women, not the symptoms of the disease, but the most serious is the long-term effects of the reproductive system.. out of 100 women were attending different hospitals in Baghdad included the Gynaecology Departments of Women Health Center at Al-Elwyia Obstetrics Hospital . Ibn Al balady Maternity and Children’s Hospital , Kamal al-Samarrai hospital Fertility Center infertility treatment and In Vitro Fertilization ( IVF ) (20 control and 80 women with infertility) DNA was extracted from the Endocervical Swabs of all infertili women, to investigate the bacteria by using Real time -PCR technique and another swab were subjected to direct Rapid Test . The venous blood sample was obtained, serum were diagnosis by Anti- Chlamydia trachomitis Chlamydia trachomitis IgG ELISA.The result of the Real time-PCR revealed was significant associated with infertility women (OR= 0.733; 13.75%, P= 0.041), among 80 infertili women, while was no significant diagnosis by ELISA (OR= 0.063; 2.50%, p= 0.095). and no significant associated with Rapid Test .In summary Real time-PCR has the possibility to contribute in the primary screening for infertility in women.